2019
DOI: 10.1158/1538-7445.sabcs18-ot2-07-01
|View full text |Cite
|
Sign up to set email alerts
|

Abstract OT2-07-01: DETECT V/CHEVENDO – Comparison of dual HER2-targeted therapy with trastuzumab plus pertuzumab in combination with chemo- or endocrine therapy in addition with CDK4/6 inhibition in patients with HER2-positive and hormone-receptor positive metastatic breast cancer

Abstract: Background: Metastatic breast cancer (MBC) is usually an incurable disease and maintenance of quality of life (QoL) is one of the main aims of therapy. In patients with HER2-positive MBC taxane-based chemotherapy in combination with dual HER2 targeted therapy with trastuzumab and pertuzumab,is the standard of care. Adverse events are well-known side effects of any cytostatic treatment and can seriously impact the patients' QoL. The synergistic combination of dual HER2-targeted therapy with trast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Other trials are investigating the efficacy and safety of dual anti-HER2 blockade in association with CDK4/6I and ET. In particular, the CHEVENDO trial is a randomized phase III study comparing the safety and efficacy of trastuzumab plus pertuzumab and the CDK4/6i ribociclib in combination with either ET or CT [77]. The phase III PATINA trial wants to investigate the advantage of combining palbociclib with trastuzumab with or without pertuzumab and ET maintenance therapy after induction therapy in the first-line setting for HR-positive/HER2-positive metastatic BC [78].…”
Section: Metastatic Settingmentioning
confidence: 99%
“…Other trials are investigating the efficacy and safety of dual anti-HER2 blockade in association with CDK4/6I and ET. In particular, the CHEVENDO trial is a randomized phase III study comparing the safety and efficacy of trastuzumab plus pertuzumab and the CDK4/6i ribociclib in combination with either ET or CT [77]. The phase III PATINA trial wants to investigate the advantage of combining palbociclib with trastuzumab with or without pertuzumab and ET maintenance therapy after induction therapy in the first-line setting for HR-positive/HER2-positive metastatic BC [78].…”
Section: Metastatic Settingmentioning
confidence: 99%
“…Potential additional benefit of the utilisation of other therapeutic approaches is currently undergoing clinical investigation, such as the synergistic combination of endocrine therapy plus dual HER2-targeted therapy and a CDK4/6 inhibitor in patients with ER+/HER2+ metastatic disease ( Krause et al 2019 ). Recently, data from the prospective, open-label, multicentre phase-II SOLTI-1303 PATRICIA trial showed that palbociclib in combination with trastuzumab is safe and results in longer PFS in trastuzumab pre-treated ER+/HER2+ advanced breast cancer with a PAM50 luminal subtype (12.4 months vs 4.1 months; P = 0.025) ( Ciruelos et al 2020 ).…”
Section: Therapeutic Strategies To Combat Endocrine Resistancementioning
confidence: 99%